Effects of controlled thermal processing and formulation on nutrients and taurine in brunok (Acaudina molpadioides) beverage: Pengaruh pemanasan terkontrol dan formulasi terhadap nutrien dan taurin pada minuman brunok (Acaudina molpadioides) - Putri, R. Marwita Sari; Amrizal, Sri Novalina; Apriandi, Azwin; Putri, Steva Dara; Prastari, Cindytia; Rahman, R. Fathul; Salomo, Ade; Afrial, Danadipa Putra; Putra, Regi Aditya (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Brunok (Acaudina molpadioides) is a functional marine ingredient that is rich in protein, essential amino acids, minerals, and taurine. This study aimed to evaluate the effects of controlled thermal processing and formulation on the nutrient composition and taurine retention in brunok (Acaudina molpadioides)-based instant beverages. Thermal processing was conducted under constant and controlled temperature conditions at 90°C, and its effects were evaluated by comparing fresh brunok, extracts, and the final powdered products. Three formulations (MFB1–MFB3) containing ginger, Curcuma xanthorrhiza, and lemon were prepared using varying proportions of brunok and subsequently processed via spray drying. Controlled thermal treatment significantly reduced moisture content, resulting in an apparent increase in protein (17.12–46.72%) and lipid content (5.42–7.18%), primarily due to the concentration effects associated with water loss. In contrast, the essential amino acids showed a decreasing trend after processing. The taurine content increased in the extract (75.05–81.73 mg/kg), suggesting enhanced extractability during heating, but decreased in the final powdered product (66–70 mg/kg), likely due to thermal degradation and spray-drying exposure. The formulation significantly affected the amino acid composition and taurine retention, with higher brunok proportions demonstrating improved taurine preservation.